مجهودات القديس أوغسطين في نشر و تطوير الديانة المسيحية في بلاد المغرب - زغدود , محاوشة , فضيلة مسعودة (جامعة الوادي University of eloued, 2018)
"إعتبر القديس أوغسطين إستخدام الفلسفة في دراسة مسائل لاهوتيه كنقطة جوهريه لبداية التاريخ . سقوط آدم من الفردوس الأعلى وهذا ما نتج عنه إستمرار الخطيئة عند البشر لا يمكن فهم التاريخ عند القديس أوغسطين إلا من خلال الرجوع للمبادئ الأولى التي سارت عليها المسيحية للتاريخ في تفسيرها للتاريخ. دراسة القديس أوغسطين لفلسفة التاريخ بمنظور عقائدي أكثر منه منظور فلسفي عقلى، كما أن الصراع الدوناتي الكاثولكي قام على أساس العداء للسلطة ولمن كان يتعامل معها خلال المحن السابقة. إن السياسة الإمبراطوية تجاه الدوناتيين كانت نتيجة عكسية على السلطة مما زادت من شعبية وقوة الحركة الدوناتيه وتحولت الى حركه تقود معارضي الإمبراطورية الرومانية في منطقة المغرب القديم لقد ولدت حركة جدل ومناقشه من طرف القديس أوغسطين الذي نظر إليها تفسد مبادئ الديانة المسيحية هذا ما أدى الى تحالفه مع السلطة ضد هذه الحركة، كما أضعفت الحركة الدوناتيه الوجود الروماني في المغرب في محاكمة قرطاج سنة 411م ."St. Augustine considered the use of philosophy in the study of theological issues as an essential point of the beginning of history. The Fall of Adam from the Higher Paradise This is what led to the continuation of sin in humans. The history of St. Augustine can be understood only by reference to the first principles that Christianity has taken to history in its interpretation of history. St. Augustine's study of the philosophy of history is more of a doctrinal perspective than a philosophical philosophical one. The Catholic Donatical struggle was based on hostility to power and to those who had dealt with it during previous tribulations. The imperialist policy towards the Donuts was an adverse reaction to power, which increased the popularity and power of the Donut movement and turned into a movement that led the opponents of the Roman Empire in the area of ​​ancient Morocco. A polemic was born and discussed by St. Augustine, who viewed it as corrupting the principles of Christianity. Authority against this movement, as the movement of the Pontifical Moroccan presence in Morocco weakened in the trial of Carthage in 411 AD."
مذكرة ماستر تاريخ تخصص حضارات قديمة
Keywords: مجهودات - القديس - أوغسطين - الديانة - المسيحية - نشر - تطوير; Efforts - Saint - Augustine - Religion - Christianisme - Edition - Développement.; Efforts - Saint - Augustine - Religion - Christianity - Publishing - Development.